Analisis Pengaruh Rasio Keuangan Terhadap Perubahan Laba Pada Perusahaan Wholesale and Retail Trade Yang Terdaftar Di Bursa Efek Indonesia (Periode 2009 - 2012) - Grisely '; Yesi Mutia Basri; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study is to demonstrate empirically the effect of Liquidity Ratio (Current Ratio), Leverage Ratio (Debt Ratio), Activity Ratio (Total Asset Turnover), Profitability Ratios (Return on Assets and Return on Equity), and Profit Margin Ratio (Gross Profit Margin) on Earnings Changes in Wholesale and Retail Trade Companies. The study used 27 companies from the Wholesale and Retail Trade sector. This research used secondary data type. The analysis method used in this research is multiple linear regression model. The study concluded that only four independent variables that have influence on the Earnings Change, they are Current Ratio (CR), Debt Ratio (DR), Return on Assets (ROA) and Return on Equity (ROE). While the variable Total Assets Turnover (TAT) and the Gross Profit Margin (GPM) have no influence on earnings changes.Keywords : Current Ratio, Debt Ratio, Total Asset Turnover, Return on Assets, Return on Equity, Gross Profit Margin, Profit Change